Unveiling the mechanisms of the UV/chlorine process for water treatment - Dharwadkar, Sripriya Manoj (Cranfield University, 2025)
Pesticides in drinking water pose public health risks and challenges for water utilities. Advanced oxidation processes (AOPs), such as UV/H2O2, are increasingly used for pesticide degradation. UV/chlorine has emerged as an alternative because of its lower chemical requirements and compatibility with UV-LEDs. However, the complex photochemistry of UV/chlorine and its impact on radical generation and downstream water quality need to be elucidated. This research compared UV/H2O2 and UV/chlorine for the removal of five pesticides commonly detected in the East of England drinking water sources (metazachlor, propyzamide, quinmerac, flufenacet and clopyralid), evaluated their impact on disinfection by-product (DBP) formation, and determined the effectiveness of activated carbon (AC) post-treatment. For pesticide degradation, the UV/chlorine process was evaluated at three irradiation wavelengths (254, 275 and 295 nm) and two pH conditions (6 and 9), reflecting various chlorine absorbance and speciation conditions. Four methods were assessed to measure UV irradiance in the 275 and 295 nm UV-LED reactors, which differed from the conventional 254 nm collimated beam in geometry and emission wavelength. Ferrioxalate actinometry was identified as the most accurate method. UV/H2O2 achieved higher pesticide degradation rates than UV/chlorine using optimised doses of 20 mg/L H2O2 and 4 mg/L chlorine. UV/chlorine was impacted by both pH and wavelength of irradiation, with optimal degradation rates at pH 6 and 254 nm due to higher radical generation. At pH 6, 254 nm was more effective than 275 and 295 nm, while at pH 9 the wavelengths were comparable except for metazachlor and flufenacet, which underwent photolysis at 254 nm. Second-order rate constants for the reactions of hydroxyl radicals (HO•) and radical chlorine species (RCS) with the pesticides are presented, with some reported for the first time. DBP formation potential tests, using tannic acid (TA) as a model natural organic matter compound, showed similar increases in chloroform (CF) yield (25%) following both AOPs. Haloacetic acid (HAA) yield increased following UV/chlorine at 200 mJ/cm2, then remained constant at higher UV doses, while following UV/H2O2 it decreased then increased at higher UV doses. Non-target analysis of transformation products (TPs) identified smaller, more chlorinated compounds formed during UV/chlorine than UV/H2O2. Correlations between TPs and regulated DBPs identified TA, digallic acid and gallic acid as precursors for HAA and CF. Pathways leading to formation of regulated and unregulated DBPs were proposed. The TPs formed had increased oxidation states relative to TA and were more hydrophilic. These were still removed by AC when applied as a post-treatment, leading to comparable dissolved organic carbon reductions between the AOPs and subsequent decreases in CF and HAA yields by 79-96% and 89-99%, respectively. These findings improve the mechanistic understanding of AOPs and inform strategies to optimise pollutant removal while managing DBP risks in drinking water.
Jarvis, Peter - Associate Supervisor
Keywords: Advanced oxidation process; pesticides; micropollutants; disinfection by-products; precursors; transformation products